2013
DOI: 10.1016/j.juro.2013.01.087
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy, Safety and Tolerability of Collagenase Clostridium Histolyticum for the Treatment of Peyronie Disease in 2 Large Double-Blind, Randomized, Placebo Controlled Phase 3 Studies

Abstract: IMPRESS I and II support the clinical efficacy and safety of collagenase C. histolyticum for the physical and psychological aspects of Peyronie disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
412
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 393 publications
(443 citation statements)
references
References 20 publications
13
412
0
18
Order By: Relevance
“…Most patients in Study 3 received three injections of CCH. This is consistent with studies of CCH for Dupuytren's contracture [1,5,10] and in clinical trials of CCH for Peyronie's disease using multiple injections [3]. Compared with other clinical studies of conservative treatment of adhesive capsulitis [2,6,8,9,11], CCH injections in Study 3 allowed patients to achieve improved ROM, functional status, and pain relief in a shorter time.…”
Section: Discussionsupporting
confidence: 83%
“…Most patients in Study 3 received three injections of CCH. This is consistent with studies of CCH for Dupuytren's contracture [1,5,10] and in clinical trials of CCH for Peyronie's disease using multiple injections [3]. Compared with other clinical studies of conservative treatment of adhesive capsulitis [2,6,8,9,11], CCH injections in Study 3 allowed patients to achieve improved ROM, functional status, and pain relief in a shorter time.…”
Section: Discussionsupporting
confidence: 83%
“…This post hoc analysis included data from 2 published clinical trials 27 that evaluated the safety and efficacy of CCH injection in patients with PD (ClinicalTrials.gov identifiers: IMPRESS-I, NCT01221597; IMPRESS-II, NCT01221623). Data were included from patients in a predefined modified intention-to-treat (mITT) population of IMPRESS-I and IMPRESS-II (ie, mITT defined as patients with both a curvature deformity measurement and a PD symptom bother score at screening who received ≥1 injection of study drug and ≥1 postinjection measurement).…”
Section: Methodsmentioning
confidence: 99%
“…27 Briefly, both were double-blind, placebocontrolled, multicenter, 52-week, phase 3 trials that recruited patients from Australia and the United States starting in September 2010 for both studies and ending in March 2012 (IMPRESS II) and April 2012 (IMPRESS I). Eligible patients were men ≥18 years of age with stable PD (diagnosis of PD for ≥12 months) and a penile curvature of 30-90 degrees who were in a heterosexual relationship and participated in vaginal intercourse.…”
Section: Methodsmentioning
confidence: 99%
“…It works by breaking down the extra collagen in the penis that causes this disease [115]. A multicenter, double-blind, phase 3 randomized and placebo-controlled trial supports the efficacy and safety of intralesional CCH in the treatment of the subjective and objective aspects of significant Peyronie's disease in patients with curvature between 30° and 90° [116,117]. Recent studies demonstrated that CCH treatment administered in multiple cycles led to significant benefit in both the psychological and physical aspects of Peyronie's disease.…”
Section: Collagenase As Debriding Agent In Wound Healingmentioning
confidence: 83%